Hubungan Kepatuhan Pembatasan Asupan Cairan dengan Kulitas Hidup Pasien Gagal Ginjal Kronik - Vitaliana Chesar, Putri Reishi; Fauzan, Suhaimi; Fradianto, Ikbal (Madago Nursing Journal, 2024)
Fluid restriction is an important part of the management of chronic kidney disease (CKD) patients to control the body's fluid balance, including both intake and excretion. Proper implementation of fluid restriction is essential to prevent further complications and improve the quality of life for CKD patients. Therefore, this study aims to examine the relationship between adherence to fluid restriction and the quality of life of CKD patients at Dr. Soedarso Hospital, Pontianak. Thin study to determine correlation between adherence to restriction fluid intake and quality of life in patients with chronic kidney disease at Dr. Soedarso Pontianak. This study employed a quantitative design with a cross-sectional correlation analysis approach. The sample consisted of 92 CKD patients selected using purposive sampling. Data were collected through questionnaires regarding adherence to fluid restriction and the quality of life of the patients. The hypothesis test used the Spearman rank correlation test with a significance level of ρ-value < 0.05. Most of the respondents were of productive age (88%), with the majority being male (52%). Nearly half of the respondents had a higher education level (40.2%). The results showed that the majority of respondents had a fairly good quality of life (81.3%) and demonstrated good adherence to fluid restriction. A significant relationship was found between adherence to fluid restriction and the quality of life of CKD patients at Dr. Soedarso Hospital, Pontianak, with a ρ-value < 0.05 and a correlation coefficient of 0.620. This relationship indicates a strong and positive association, meaning that the better the adherence to fluid restriction, the better the quality of life of the patients.